Association between fetal hemoglobin, lactate dehydrogenase, and disease severity in patients with sickle cell disease at Bugando Medical Centre, Mwanza, Tanzania - Kahema, Samwel Edward; Mbulwa, Cosmas H.; Bagenda, Charles Nkubi; Niyonzima, Nixon; Muwanguzi, Enoch; Mcharo, Tunzo L. (Plos one, 2024)
Introduction: There is a wide range of clinical manifestations in sickle cell disease (SCD). Despite having the same condition, each person’s response to disease complications differs greatly. Individuals can be categorized according to the severity of their diseases to determine which group they fall into and receive the appropriate care based on their needs. The relationship between fetal hemoglobin (HbF), lactate dehydrogenase (LDH), and disease severity in Tanzania is little understood. This investigation sought to ascertain the relationship between HbF, LDH, and disease severity in SCD patients at the Bugando Medical Center. Method: This cross-sectional study was carried out on SCD patients aged 6 months and older at the Bugando Medical Center in Mwanza, Tanzania. A total of 130 SCD patients were enrolled. The clinical history and laboratory test results for SCD patients were recorded on a specially constructed patient report form. Results: The majority of participants (56.9%) were men. For the population under study, more than half (60.8%) of participants had a moderate clinical phenotype (MCP), followed by 31.5% of asymptomatic participants and 7.7% of people with severe clinical phenotypes (SCP). Participants with SCP had substantially higher levels of LDH, with a mean level of 810.97IU/L (95% CI: 559.31–1062.64) and a p-value of 0.005. The severe clinical phenotype exhibited a significantly higher mean HbF score value of 10.09% (95% CI: 7.44–13.74%) with a p-value of 0.024 when compared to the asymptomatic and moderate clinical phenotypes. Conclusion: In SCD patients with SCP compared to ACP and MCP, the HbF levels were higher, but did not show a protective effect, and LDH can be used to predict the severity of SCD.
Keywords: Fetal hemoglobin; Lactate dehydrogenas; Disease severity; Patients; Sickle cell disease